Electrical and optical characterizations of carbon nanotubes - Lin, Yiding. (2011)
Electrical and optical characterizations of carbon nanotubes were investigated in this thesis. Main objectives were focused on electrical characterizations of SWNT bundles in high frequency regime and electrical and optical characterizations of carbon nanotube thin films on glass substrate. To achieve the former objective, S-Parameters for each CPW sample were extracted from Vector Network Analyzer for SWCNT high frequency performance evaluation and their relation to corresponding DC resistances was found and discussed. The relation between CNT bundle numbers and S-Parameters as well as DC resistance was also briefly investigated, though much more effort will be made on that topic. In latter objective, a self-designed transmittance measurement system was made and used for CNT thin film samples optical characterization. The corresponding electrical property (i.e. sheet resistance) was determined by four-point probe. The relation between sheet resistance and optical transmittance for CNT thin film samples was also established at the end.